Synaptic gene dysregulation within hippocampal CA1 pyramidal neurons in mild cognitive impairment - Counts, Scott E.; Alldred, Melissa J.; Che, Shaoli; Ginsberg, Stephen D.; Mufson, Elliott J. (Neuropharmacology, 2014)
Clinical neuropathologic studies suggest that the selective vulnerability of hippocampal CA1 pyramidal projection neurons plays a key role in the onset of cognitive impairment during the early phases of Alzheimer's disease (AD). Disruption of this neuronal population likely affects hippocampal pre- and postsynaptic efficacy underlying episodic memory circuits. Therefore, identifying perturbations in the expression of synaptic gene products within CA1 neurons prior to frank AD is crucial for the development of disease modifying therapies. Here we used custom-designed microarrays to examine progressive alterations in synaptic gene expression within CA1 neurons in cases harvested from the Rush Religious Orders Study who died with a clinical diagnosis of no cognitive impairment (NCI), mild cognitive impairment (MCI, a putative prodromal AD stage), or mild/moderate AD. Quantitative analysis revealed that 21 out of 28 different transcripts encoding regulators of synaptic function were significantly downregulated (1.4–1.8 fold) in CA1 neurons in MCI and AD compared to NCI, whereas synaptic transcript levels were not significantly different between MCI and AD. The downregulated transcripts encoded regulators of presynaptic vesicle trafficking, including synaptophysin and synaptogyrin, regulators of vesicle docking and fusion/release, such as synaptotagmin and syntaxin 1, and regulators of glutamatergic postsynaptic function, including PSD-95 and synaptopodin. Clinical pathologic correlation analysis revealed that downregulation of these synaptic markers was strongly associated with poorer antemortem cognitive status and postmortem AD pathological criteria such as Braak stage, NIA-Reagan, and CERAD diagnosis. In contrast to the widespread loss of synaptic gene expression observed in CA1 neurons in MCI, transcripts encoding β-amyloid precursor protein (APP), APP family members, and regulators of APP metabolism were not differentially regulated in CA1 neurons across the clinical diagnostic groups. Taken together, these data suggest that CA1 synaptic gene dysregulation occurs early in the cascade of pathogenic molecular events prior to the onset of AD, which may form the basis for novel pharmacological treatment approaches for this dementing disorder. This article is part of a Special Issue entitled ‘Neurodegenerative Disorders’. •Hippocampal CA1 neurons display widespread synaptic gene downregulation in MCI and AD.•Genes encoding APP and APP family members were unaffected in MCI and AD.•Synaptic mRNA levels correlate with poorer cognition and increased AD pathology.•CA1 synaptic dysregulation is a very early pathogenic event in AD.